Chapter: 'Enhancing Public Speaking Skills - An Evaluation of the Presentation Trainer in the Wild' from book: Adaptive and Adaptable Learning: 11th European Conference on Technology Enhanced Learning, EC-TEL 2016, Lyon, France, September 13-16, 2016, Proceedings - Dirk Börner; Peter van Rosmalen; Jan Schneider; Marcus Specht (Springer Nature, 2016)
The increasing accessibility of sensors allows the study and development of multimodal learning tools that create opportunities for learners to practice while receiving feedback. One of the potential learning scenarios addressed by these learning applications is the development of public speaking skills. First applications and studies showed promising empirical results in laboratory conditions. In this article we present a study where we explored the use of a multimodal learning application called the Presentation Trainer, supporting learners with a real public speaking task in the classroom. The results of this study help to understand the challenges and implications of testing such a system in a real-world learning setting, and show the actual impact compared to the use in laboratory conditions.
English
Keywords: learning support; application; multimodal learning; public speaking; sensor-based learning